Allium jichouense (Amaryllidaceae), a new species of the section Sikkimensia from southwestern China - Huang, De-Qing; Sun, Hang; Ma, Xiang-Guang (Phytotaxa, 2022)
Allium jichouense from Sichuan Province, southwestern China is described as a new species. It grows exclusively on alpine screes or gravelly slopes at higher altitudes of 4,300–4,500 m. Morphologically, it resembles A. sikkimense in bulb and floral features, but differs significantly in its falcate or curled, commonly reddish-purple pigmented leaves, scapes and spathe-valves. Phylogenetic analyses confirm that the new species belongs to A. sect. Sikkimensia and is nested within different populations of A. sikkimense. The possible scenarios are discussed for the embedded phylogenetic relationship of A. jichouense within A. sikkimense. A detailed morphological description, illustrations and habit features of the new species are given.